Optimalisasi Manajemen Sarana Prasarana di PAUD Nurul Ihsan Tanjung Jabung Timur - Mahmud MY; Riftiyanti Safitri; Dwika Ristanti (JMiE (Journal of Management in Education), 2022)
This study aims to describe the process of infrastructure management at PAUD Nurul Ihsan Tanjung Jabung Timur which includes the procurement, distribution, maintenance and inventory of infrastructure. One of the efforts in improving the quality of PAUD is to meet adequate, quality infrastructure, in accordance with early childhood development, and ready-to-use infrastructure. Therefore, to improve the quality of PAUD, a good management of infrastructure is needed. This research uses a qualitative approach. Data collection is carried out through observation, interviews, and documentation. The results showed that the procurement of infrastructure was carried out from the disbursement of BOP (Educational Operational Assistance) funds, community contributions and parents of students. Maintenance is carried out by educators and education personnel. Inventory is carried out recording goods for each receipt of infrastructure.